Adverse Effects of Gadolinium-Based Contrast Agents: Changes in Practice Patterns. Issue 4 (August 2016) - Forghani, Reza
Abstract : Abstract: Gadolinium-based contrast agents have been used for magnetic resonance imaging (MRI) examinations since the late 1980s with an excellent overall cumulative safety record. Initially favored for use in patients with renal impairment because of lack of significant nephrotoxic effect at clinical doses, in 2006, multiple reports convincingly linked the rare but serious disease nephrogenic systemic fibrosis to the administration of gadolinium-based contrast agents in patients with severe renal failure. This in turn led to new policies on administration of these agents, resulting in changes in practice patterns that have virtually resulted in the elimination of the disease after the year 2009. The purpose of this review is to summarize the factors that led to the emergence of nephrogenic systemic fibrosis, including the risk associated with different types of contrast agents based on their stability, and the changes in practice patterns and usage of gadolinium-based contrast agents in recent years that have been mainly driven by the discovery and association with nephrogenic systemic fibrosis. The article will conclude with a brief overview of new emerging safety concerns that could further impact the use of this class of contrast agents and impact practice patterns in the future.